Isolating Personal Knowledge Spillovers: Coinventor Deaths and Spatial Citation Differentials - Balsmeier, Benjamin; Fleming, Lee; Lück, Sonja (American Economic Review: Insights)
We propose a new method to estimate and isolate the localization of knowledge spillovers due to the physical presence of a person, using after-application but pre-grant deaths of differently located coinventors of the same patent. The approach estimates the differences in local citations between the deceased and still-living inventors at increasingly distant radii. Patents receive 26 percent fewer citations from within a radius of 20 miles around the deceased, relative to still-living coinventors. Differences attenuate with time and distance, are stronger when still-living coinventors live farther from the deceased, and hold for a subsample of possibly premature deaths. (JEL O31, O33, O34, R32)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Feasibility Study of Compression Molding for Large Reinforcement Structures in the Commercial Vehicle Sector - Lückenkötter, Julian; Leimbach, J.P.; Stallmeister, Tim; Marten, Thorsten; Tröster, Thomas (Materials Research Proceedings)
Abstract. Due to an increasing volume of shipments, there is a significant need for more delivery vehicles. One approach to reduce the associated increase in carbon dioxide (CO2) emissions is a new light weight design approach involving the substitution of conventional materials with glass fiber mat-reinforced thermoplastics (GMT) based on polypropylene (PP). The application of GMT by compression molding is a widely used process in the automotive industry. However, application in the commercial vehicle sector requires much larger dimensions, making it necessary to clarify whether the manufacturing process and material are suitable for semi-structural applications on this scale. To find this out, two replacement geometries are abstracted in this study and manufactured by varying the main manufacturing parameters. The feasibility can be demonstrated by recording and analyzing the resulting process variables and measuring the formed fiber distribution. At the end of the paper, recommendations are given for the production of GMT structures on the scale of commercial vehicles.
Keywords: Compression Molding; Fiber Content; Process Development; Lightweight Design

A Validation Study for the German Versions of the Feeling Scale and the Felt Arousal Scale for a Progressive Muscle Relaxation Exercise - Thorenz, Kristin; Berwinkel, Andre; Weigelt, Matthias (Behavioral Sciences)
The aim of the present study is to prove the construct validity of the German versions of the Feeling Scale (FS) and the Felt Arousal Scale (FAS) for a progressive muscle relaxation (PMR) exercise. A total of 228 sport science students conducted the PMR exercise for 45 min and completed the FS, the FAS, and the Self-Assessment Manikin (SAM) in a pre-test–post-test design. A significant decrease in arousal (t(227) = 8.296, p < 0.001) and a significant increase in pleasure (t(227) = 4.748, p < 0.001) were observed. For convergent validity, the correlations between the FS and the subscale SAM-P for the valence dimension (r = 0.67, p < 0.001) and between the FAS and the subscale SAM-A for the arousal dimension (r = 0.31, p < 0.001) were significant. For discriminant validity, the correlations between different constructs (FS and SAM-A, FAS and SAM-P) were not significant, whereas the discriminant analysis between the FS and the FAS revealed a negative significant correlation (r = −0.15, p < 0.001). Together, the pattern of results confirms the use of the German versions of the FS and the FAS to measure the affective response for a PMR exercise.
Keywords: Behavioral Neuroscience; General Psychology; Genetics; Development; Ecology; Evolution; Behavior and Systematics

Design approach to extend and decarbonise existing district heating systems - case study for German cities - Divkovic, Denis; Knorr, Lukas; Meschede, Henning (International Journal of Sustainable Energy Planning and Management)
This paper aims to present an approach for the planning of carbon low heat supply in a future district heating system based on open data for German cities with existing district heating networks. One focus is on the integration of industrial waste heat and the uncertainty of future waste heat sources as well as restrictions on the use of biomass. For that purpose, knowledge about the energy demand is necessary. In a first step it is shown how the demand around a heating network is estimated with spatial data and a load profile is generated. Local available heat sources are examined according to their suitability and their kind of integration in the heating network. As heat production from different units are optimised, the development of a simulation model will be presented. The simulation is based on the optimisation of the operational costs of the used technologies for heating supply. Different scenarios covering various technologies and economic assumptions are applied. The results show the levelized costs of heating as well as the ecological performance. A sensitivity analysis shows the importance of uncertainties for the economic assumptions. The results showing levelized costs of heating as well as the ecological performance underlining the advantage of excess heat integration.
Keywords: Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

A hybrid multi-attribute decision-making and data envelopment analysis model with heterogeneous attributes: The case of sustainable development goals - Soltanifar, Mehdi; Tavana, Madjid; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Environmental Science & Policy)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Situational Business Model Developer: A Tool-support for Situation-speciﬁc Business Model Development - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 17th International Conference on Wirtschaftsinformatik)
The development of business models is a challenging task that can be supported with software tools. Here, existing approaches and tools do not focus on the company’s situation in which the development takes place (e.g., ﬁnancial resources, product type). To tackle this challenge, we used design science research to develop a situation-speciﬁc business model development approach that contains three stages: First, existing knowledge in terms of tasks to do (e.g., analyze competitive advantage), and decisions to be made (e.g., social media marketing) are stored in repositories. Second, the knowledge is used to compose a development method based on the company’s situation. Third, the development method is enacted to develop a business model. This demonstration paper presents a tool-support called Situational Business Model Developer that supports all stages of our approach. We release the tool under open-source and evaluate it with a case study on developing business models for mobile apps.
Keywords: Business Model Development; Situational Method Engineering; Tool Support

Agency: Taking Stock of Workplace Learning Research - Goller, Michael; Paloniemi, Susanna (Research Approaches on Workplace Learning)
This chapter presents a discussion of the concept of agency. Agency is understood as a multifaceted construct describing the idea that human beings make choices, act on these choices, and thereby exercise influence on their own lives as well as their environment. We argue that the concept is discussed from three different perspectives in the literature—transformational, dispositional, and relational—that are each related to learning and development in work contexts. These perspectives do not reflect incompatible positions but rather different aspects of the same phenomena. The chapter also offers an avenue of insight into empirical studies that employ agency as a central concept as well as discussions about concepts that closely overlap with ideas of human beings as agents of power and influence.
Keywords: Agency Workplace learning Professional development Proactivity Self-direction

AI Assisted Interference Classification to Improve EMC Troubleshooting in Electronic System Development - Maalouly, Jad; Hemker, Dennis; Hedayat, Christian; Rückert, Christian; Kaufmann, Ivan; Olbrich, Marcel; Lange, Sven; Mathis, Harald (2022 Kleinheubach Conference)
In this paper, machine learning techniques will be used to classify different PCB layouts given their electromagnetic frequency spectra. These spectra result from a simulated near-field measurement of electric field strengths at different locations. Measured values consist of real and imaginary parts (amplitude and phase) in X, Y and Z directions. Training data was obtained in the time domain by varying transmission line geometries (size, distance and signaling). It was then transformed into the frequency domain and used as deep neural network input. Principal component analysis was applied to reduce the sample dimension. The results show that classifying different designs is possible with high accuracy based on synthetic data. Future work comprises measurements of real, custom-made PCB with varying parameters to adapt the simulation model and also test the neural network. Finally, the trained model could be used to give hints about the error’s cause when overshooting EMC limits.
Keywords: emc; pcb; electronic system development; machine learning; neural network

Review of Design-Oriented Green Information Systems Research - Brendel, Alfred Benedikt; Chasin, Friedrich; Mirbabaie, Milad; Riehle, Dennis M.; Harnischmacher, Christine (Sustainability)
Green IS (GIS) research addresses environmental challenges brought on by climate change and the need to preserve the natural environment. Within this scope, design-oriented research, most notably within the Design Science Research (DSR) community, aims to provide solutions to these environmental challenges in the form of novel artifacts. The resulting IS solutions are valuable instruments for reducing emissions, increasing energy efficiency, and mitigating waste. Over the past 14 years, the IS research community was called upon multiple times to focus on designing solutions suitable for facilitating sustainability. However, it is unclear how these calls for action resonated within the design-oriented research community. Against this background, we analyzed the landscape of design-oriented GIS research by looking at 60 different GIS studies that have designed and evaluated an artifact. By analyzing these publications, we were able to make six observations. Based on these observations, we discuss how design-oriented GIS research can evolve to live up to the expectations of creating an immediate positive environmental impact.
Keywords: Management; Monitoring; Policy and Law; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

Continuous Situation-specific Development of Business Models: Knowledge Provision, Method Composition, Method Enactment - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (International Journal on Software and Systems Modeling (SoSyM))
The development of new business models is essential for startups to become successful, as well as for established companies to explore new business opportunities. However, developing such business models is a continuous challenging activity where different tasks need to be performed, and business decisions need to be made. Both have to fit the constantly changeable situation in which the business model is developed to reduce the risk of developing ineffective business models with low market penetration. Therefore, a method for developing situation-specific business models is needed. As a solution, we refine the concept of situational method engineering (SME) to business model development. SME, in turn, provides means to construct situation-specific development methods out of fragments from a method repository. We develop a concept for the continuous situation-specific development of business models based on design science. The approach uses the roles of a domain expert, a method engineer, and a business developer together with a repository with method fragments for developing business models and a repository with modeling artifacts for supporting the development. Both repositories are filled by utilizing the experience of domain experts. Out of these repositories, situation-specific development methods for developing business models can be continuously composed based on the changeable situation by the method engineer and enacted by the business developer. We implement it as an open-source tool and evaluate its applicability in an industrial case study of developing a business model for a local event platform. Our results show that situation awareness supports the continuous development of business models.
Keywords: Business Model Development; Situational Method Engineering; Situation-specific; Business Model Canvas; Continuous Development